2020
DOI: 10.1016/j.bbi.2020.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immune response and self-reported depression during convalescence from COVID-19

Abstract: Self-reported depression has been observed in coronavirus disease-2019 (COVID-19) patients, infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), during discharge from the hospital. However, the cause of this self-reported depression during the convalescent period remains unclear. Here, we report the mental health status of 96 convalescent COVID-19 patients who were surveyed using an online questionnaire at the Shenzhen Samii Medical Center from March 2 to March 12, 2020 in Shenzhen, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 25 publications
3
75
0
4
Order By: Relevance
“…Given the great influence of COVID-19 on people globally, investigating how COVID-19 may affect the mental health of people is an urgent issue. Precious studies have investigated how the COVID-19 crisis, particularly the lockdown and quarantine policies, affects people’s mental health [ 1 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. However, few studies have shown how the risk perception of COVID-19 may affect people’s mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the great influence of COVID-19 on people globally, investigating how COVID-19 may affect the mental health of people is an urgent issue. Precious studies have investigated how the COVID-19 crisis, particularly the lockdown and quarantine policies, affects people’s mental health [ 1 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. However, few studies have shown how the risk perception of COVID-19 may affect people’s mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also evidence of prevalent depressive symptoms in those already recovered from COVID-19 (Cai et al, 2020;Yuan et al, 2020;Zhang et al, 2020). A study of 126 COVID-19 survivors in convalescence from Shenzhen, China, showed that self-reported anxiety and depression were common after discharge from hospital (Cai et al, 2020) and moreover, depressive symptoms were associated with immune systemic suppression, based on increased white blood cells and inflammatory factors measures (Yuan et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 99%
“…The patient could rate each question from 0 to 3 to provide a severity score ranging from 0 to 27. We de ned depression severity as being no depression (1-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), moderately severe depression (15)(16)(17)(18)(19), and severe depression (20)(21)(22)(23)(24)(25)(26)(27). We considered signi cant depression to be present when the total score was 10 or higher.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological morbidities, including PTSD, anxiety, and depression, were reported to be common in COVID-19 patients [12]. Additionally, immune function changes correlated with self-reported depression during short-term follow-up of COVID-19 patients following discharge from the hospital [19].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation